Predictors of Persistence of Anxiety, Hyperarousal Stress, and Resilience During the COVID-19 Epidemic: A National Study in Iran - Sharif Nia, Hamid; Akhlaghi, Elham; Torkian, Samaneh; Khosravi, Vahid; Etesami, Reza; Froelicher, Erika Sivarajan; Pahlevan Sharif, Saeed (Frontiers in Psychology, 2021)
Background: Coronavirus pandemic can cause unprecedented global anxiety and in contrast, resilience can help people's mental health in stressful situations. This study aims to assess anxiety, hyperarousal stress, resilience of the Iranian population and their related factors during the coronavirus disease 2019 )COVID-19( epidemic. Methods: A cross-sectional study was conducted in 31 provinces in Iran in the second week of March 2020 from 18 March to 25 March when the epidemic started. A four-part questionnaire, including demographic information, the State-Trait Anxiety Inventory (a 20-item standard questionnaire for obvious anxiety-(STAI-y1)), the Connor-Davidson Resilience Scale (CD-RISC- a 25-item) and stress hyperarousal subscale from the Impact of Event Scale-Revised (IES-R) was used to collect data. The ordinal multivariable Generalized Estimating Equations (GEE) model was used to identify correlates of the psychological factors mentioned above. The Chi-squared test was used to investigate the relationship between covid-19 outbreak with anxiety, stress and resilience. all analyses were conducted with SPSS26 and GIS10.71. Results: The findings show that most people had moderate to severe anxiety (80.17%), and a high level of resilience (96.4%) during the COVID 19 epidemic. The majority of participants had moderate stress (58.9%). The lowest and highest prevalence of psychiatric disorders was in Sistan & Baluchistan and Semnan provinces, respectively. Gender (Male) and marital status (single and being widowed/ Divorced) were the only variables statistically significantly associated with anxiety and resilience. Age, gender and education were statistically significantly associated with hyperarousal stress. Have Conclusion: The high and moderate levels of anxiety and stress in Iran can have negative effects on people's well-being and performance and can lead to serious problems. Also, high resilience and negative life events are associated with well-being in people's lives. The results of this study can be used in interventions and other psychological studies.